Peningkatan Kreativitas Peserta Didik Menggunakan Model Pembelajaran Project Based Learning: Improving Student Creativity Through Project-Based Learning - Ni’mah , Ummi Lailatun (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Here's a well-formatted English translation of the abstract, adhering to proper grammar and academic conventions: Ummi Lailatun Ni'mah Master's Program in MIPA Education, Postgraduate Faculty Universitas Indraprasta PGRI Email: lailatunnimah@gmail.com Abstract This research is a classroom action research aiming to determine the increase in student creativity using the Project-Based Learning model in Physics learning for Class XI MIPA 1 at SMAS Daarul Qur'an Cikarang in the 2024/2025 Academic Year. The research procedure was carried out through three cycles: Cycle I focused on Kepler's Laws with the product being teaching aids; Cycle II focused on Newton's Law of Universal Gravitation with the product being posters; and Cycle III focused on the Law of Conservation of Momentum with the product being modified simple water rockets. The subjects of this research were 25 students. The object of this study was student creativity using the Project-Based Learning model. Data collection techniques included observation and documentation. The research results indicate that Cycle I, Cycle II, and Cycle III showed an increase in product, project, creativity, and student learning outcomes. This is evident from the qualitative descriptive data analysis of the learning process from Cycle I to Cycle III. Furthermore, the quality of the increase in student creativity was analyzed using percentages. In Cycle I, product achievement was 68.89%, project achievement was 74.44%, and creativity was 72%. In Cycle II, these increased to 80% for products, 88.9% for projects, and 88% for creativity. Subsequently, Cycle III showed a further increase, reaching 95.5% for products, 91.67% for projects, and 95% for creativity, placing it in the high category.